Multiprofessional perinatal care in a pregnant patient with acute respiratory distress syndrome due to COVID-19 - Pilar Palmrich; Bernhard Roessler; Lukas Wisgrill; Stephanie Kampf; Pia Gattinger; Rudolf Valenta; Edith Fleischmann; Angelika Berger; Herbert Kiss; Alex Farr (BMC, 2021)
Abstract Background The coronavirus disease (COVID-19) pandemic has caused ongoing challenges in health services worldwide. Despite the growing body of literature on COVID-19, reports on perinatal care in COVID-19 cases are limited. Case presentation We describe a case of severe acute respiratory distress syndrome (ARDS) in a 36-year-old G5/P2 pregnant woman with morbid obesity, confirmed severe acute respiratory syndrome coronavirus 2 infection, and fulminant respiratory failure. At 28+ 1 gestational weeks, the patient delivered an uninfected newborn. Using ImmunoCAP ISAC® technology, we found no immunoglobulin (Ig) M antibodies, suggesting that no mother-to-child viral transmission occurred during pregnancy or delivery. The maternal respiratory state improved rapidly after delivery; both maternal and neonatal outcomes were encouraging given the early gestational age and fulminant course of respiratory failure in our patient. Conclusions The management of ARDS in pregnant women with COVID-19 is complex and requires an individualized, multidisciplinary approach, while considering maternal and fetal outcomes.